Case report: Villaret's syndrome caused by middle ear adenocarcinoma in a cat - Kang, Dong-Jae; Park, Won-Keun; Kim, So-Yeon; Shin, Dong-Hoon; Park, Hee-Myung; Kang, Min-Hee (Frontiers in Veterinary Science, 2023)
A 7-year-old castrated male American Shorthair cat presented with left side Horner's syndrome and voice change. The overall clinical presentation included dysphagia, intermittent coughing, unilateral miosis and third eyelid protrusion of the left eye. A topical 1% phenylephrine was applied and miosis and protrusion of third eyelid disappeared within 20 minutes which suggested a postganglionic lesion. Laryngoscopy showed left sided laryngeal paralysis. Computed tomography (CT) identified a mass lesion invading outside of left tympanic bulla with osteolysis. Endoscopically assisted ventral bulla osteotomy was performed for tumor resection and definitive diagnosis. Middle ear adenocarcinoma was diagnosed based on histopathology. It appears that those neurological signs occurred due to adenocarcinoma in the tympanic bulla penetrated to jugular foramen and hypoglossal canal, damaging cranial nerve IX (glossopharyngeal nerve), X (vagus nerve), XI (accessory nerve), Ⅻ (hypoglossal nerve) and sympathetic nerve. To our knowledge, this is the first case report of Villaret's syndrome associated with middle ear adenocarcinoma affecting the nerves passing through the jugular foramen and hypoglossal canal in the cat.